In search of a concept for cultural mediation in libraries: conceptual contributions - Rasteli, Alessandro [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
In this study we advance a concept for cultural mediation in libraries drawing on Brazilian and French Information Science. This study took a qualitative approach and was exploratory and descriptive in nature. We combined methods of bibliographic research and field research and applied content analysis to the collected data. We found several elements that could be incorporated into a concept of cultural mediation in libraries. We proposed the following definition: Cultural mediation in libraries is the set of processes, interferences and devices that provide library customers with access to culture and thus help them build meanings and knowledge, develop socially and culturally and play greater cultural roles. Such concept of cultural mediation in libraries is related to various processes and interactions, to the construction of meanings, to the paradigms of access and democratization of culture, to cultural policies, to appropriation and to cultural leadership and proeminence.
Keywords: Cultural mediation; Cultural mediation - libraries; Librarian - cultural mediator